Managing solar retinopathy with suprachoroidal triamcinolone acetonide injection in a young girl: a case report - Ameen Marashi (BMC, 2021)
Abstract Background Solar retinopathy is a disease that causes photochemical toxicity in the retinal fovea tissues, leading to an acute decrease of vision. Case presentation This case report is an interventional case of an asymptomatic 17-year-old Caucasian female with a history of suddenly decreased vision due to solar retinopathy. The patient was managed with a custom-made needle injection of triamcinolone acetonide in the suprachoroidal space. Four months post suprachoroidal injection showed an anatomical and functional improvement in the ellipsoid zone layer through optical coherence tomography signal reappearance. In addition, the best-corrected visual acuity had improved from 0.1 to 1.0 on the Snellen chart with the disappearance of the scotoma. However, there was a mild increase in intraocular pressure after this procedure, controlled with topical hypertensive eye drops. Conclusion Suprachoroidal triamcinolone acetonide injection using a custom-made needle showed both functional and anatomical improvement of macular changes post-solar retinopathy, with acceptable safety outcomes in a young female.